CHARACTERISTIC FEATURES OF CHOOSING A PLATFORM FOR PLACEMENT OF THE WEB MULTIMEDIA ENCYCLOPEDIA «PRECEDENTAL EDUCATION» (Journal of Information Technologies in Education (ITE), 2024)
The article examines the key aspects of using web platforms for creating and hosting the electronic educational resource Web Multimedia Encyclopedia "Preschool Education". Special attention in the study is paid to the needs of users - teachers and students - which influence the strategic choice of the platform. The article examines the conditions of distance learning, in particular within the framework of web platforms. The author analyzes how these conditions affect the effectiveness of the educational process, and also highlights the challenges faced by teachers and students in the process of using digital educational resources. The relevance of using such Web multimedia encyclopedias in the educational process of specialization 012 "Preschool education" is considered. The article highlights the main advantages and disadvantages of using web platforms for training students, in particular Moodle and Canvas, taking into account the needs of users. Attention is drawn to their potential to enrich the educational environment with various visual and audiovisual materials to stimulate the cognitive and emotional development of students. The functionality and capabilities of two popular platforms - Moodle and Canvas - are compared, taking into account their compliance with the educational needs of applicants for the specialty 012 "Preschool education" education. The main emphasis is on the characterological aspects of choosing a platform, in particular, on which learning opportunities best meet the needs and contribute to the effective training of future educators. The article highlights the importance of web platforms, in particular Moodle, for the creation of electronic educational resources at Kherson State University. The authors give examples of convenient resources, such as Web multimedia encyclopedias from various disciplines, which play an important role in shaping the personality of future specialists. Taking into account the individuality of users, the article examines the influence of the choice of platform on the psychological comfort of teachers and students who actively interact with electronic educational resources.
Keywords: interactive educational environment, Web multimedia encyclopedia, preschool education, three-subject relations, three-subject didactics, Moodle, Canvas.